Synbiotic mulberry ameliorates kidney injury in dextran sodium sulfate-induced colitis rats - Keerati Wanchai; Atcharaporn Ontawong; Pairote Wongputtisin; Keerakarn Somsuan; Doungporn Amornlerdpison (Asian Pacific Journal of Tropical Biomedicine)
Objective: To investigate the effect of synbiotic mulberry on kidney injury in a dextran sodium sulfate (DSS)-induced colitis model. Methods: Male Wistar rats were given drinking water containing 4% DSS for 7 days. Subsequently, the rats were treated by oral gavage with synbiotic mulberry at 250, 500, and 1000 mg/kg, sulfasalazine at 100 mg/kg, or synbiotic at 1000 mg/kg for an additional 7 days while receiving 0.4% DSS in drinking water. The severity of colitis was evaluated based on the disease activity index score. On day 14, plasma was collected, and the kidneys were harvested to evaluate kidney injury parameters and histological changes. In addition, the expression of genes associated with kidney injury was determined by quantitative RT-PCR. Results: Treatment with all doses of synbiotic mulberry significantly lowered the disease activity index score, accompanied by reductions in kidney histopathological changes, malondialdehyde concentration, and plasma cystatin C levels. Kidney fibrosis was also ameliorated by 500 and 1000 mg/kg of synbiotic mulberry. Treatment with 250 and 500 mg/kg of synbiotic mulberry downregulated IL-18 mRNA expression, while KIM-1 mRNA expression was reduced and plasma lipopolysaccharide-binding protein level was restored by 1000 mg/kg of synbiotic mulberry. Conclusions: Synbiotic mulberry ameliorates kidney injury in rats with DSS-induced colitis. It may be further explored as a treatment of kidney injury under colitis conditions.